Increase in scout trips due to forager removal in Atta sexdens (Hymenoptera, Formicidae) (Forel, 1908) - Brugger, Mariana Silva [UNESP]; Camargo, Roberto da Silva [UNESP]; Forti, Luiz Carlos [UNESP]; Lopes, Juliane Floriano Santos (Elsevier, 2018)
Social information exchange through physical contacts and chemical trail deposition forms the basis of food recruitment in leaf-cutting ants. The scout initiates the process and passes the information to nestmates that recruit more foragers, thus amplifying the stimulus and ensuring the success of foraging. An interruption of the contact between workers and a reduction in trail laying can diminish the effectiveness of mass recruitment and alter scouting activity and forager flow. This study verified an increase in scout trips as a consequence of inbound workers (with or without a plant load) removal during Atta sexdens foraging, sustaining the outbound flow of foragers, and consequently foraging activity, either through direct contact or chemical trail deposition. Data indicate as one of the roles of unladen workers along the foraging trail must be to stimulate other workers to go out and so speed up the recruitment process The remarkable ability to organize themselves without central control is a major strength of social insects and the increase in scouting activity observed here is an example of this behavioral flexibility in leaf-cutting ants. Although foraging performance is enhanced through communication between workers, the simple adjustment in scouting activity can maintain the outbound flow of foragers which is an essential activity of the colony.
Keywords: Foraging; Interaction; Leaf-cutting ants; Recruitment; Self-organized system